Acceptance of COVID-19 vaccine among healthcare workers in Africa, systematic review and meta-analysis - Zerihun Figa; Tesfaye Temesgen; Addisu Getnet Zemeskel; Moges Ganta; Asrat Alemu; Mesfin Abebe; Zemachu Ashuro (Elsevier, 2022)
Objectives: This study is intended to assess healthcare workers' acceptance of the COVID-19 vaccine in Africa. Study design: Systematic review and meta-analysis. Method: The search was done using: PubMed, HINARI and Web of Science, African OnLine, and other gray and online repositories of Universities in Africa. All included articles were extracted and appraised using the standard data extraction sheet format of JOANNA Briggs Institute. Cochran Q test and I2 statistics test were used to test the heterogeneity of the studies. A Funnel plot and Egger's test were used to detect the publication bias of included studies. A Forest plot was used to present the pooled prevalence acceptance of the COVID-19 vaccine. Result: In this systematic review and meta-analysis thirteen cross-sectional studies and one nationwide survey with a total population of 23,739 were included. The pooled estimated prevalence of healthcare workers' acceptance of the COVID-19 vaccine in Africa was 56.59 (95%CI; 46.26-66.92; I2 = 99.6%, p = 0.000). Subgroup analysis was done using the regions in Africa, willingness to accept the COVID-19 vaccine was highest in the South African region accounting for 74.64 (95%CI; 44.16-105.11) followed by the North African region at 66.68 (95% CI; 50.74-82.62). Conclusion: The overall acceptance of the COVID-19 vaccine among healthcare workers in Africa was low. Thus, further duties should be unwavering to improve the COVID-19 vaccine acceptance by healthcare workers, through consistent and committed efforts in improving political commitment, amending strategies, improving awareness, and disclosing information about the safety, side effects, and effectiveness of the COVID-19 vaccine.